Ssy1p and Ptr3p Are Plasma Membrane Components of a Yeast System That Senses Extracellular Amino Acids - Klasson, Hanna (American Society for Microbiology, 1999)
Mutations in SSY1 and PTR3 were identified in a genetic selection for components required for the proper uptake and compartmentalization of histidine in Saccharomyces cerevisiae. Ssy1p is a unique member of the amino acid permease gene family, and Ptr3p is predicted to be a hydrophilic protein that lacks known functional homologs. Both Ssy1p and Ptr3p have previously been implicated in relaying signals regarding the presence of extracellular amino acids. We have found that ssy1 and ptr3 mutants belong to the same epistasis group; single and ssy1 ptr3 double-mutant strains exhibit indistinguishable phenotypes. Mutations in these genes cause the nitrogen-regulated general amino acid permease gene (GAP1) to be abnormally expressed and block the nonspecific induction of arginase (CAR1) and the peptide transporter (PTR2). ssy1 and ptr3 mutations manifest identical differential effects on the functional expression of multiple specific amino acid transporters. ssy1 and ptr3 mutants have increased vacuolar pools of histidine and arginine and exhibit altered cell growth morphologies accompanied by exaggerated invasive growth. Subcellular fractionation experiments reveal that both Ssy1p and Ptr3p are localized to the plasma membrane (PM). Ssy1p requires the endoplasmic reticulum protein Shr3p, the amino acid permease-specific packaging chaperonin, to reach the PM, whereas Ptr3p does not. These findings suggest that Ssy1p and Ptr3p function in the PM as components of a sensor of extracellular amino acids.